2013
DOI: 10.1007/s00395-012-0324-y
|View full text |Cite
|
Sign up to set email alerts
|

Novel mechanisms for caspase inhibition protecting cardiac function with chronic pressure overload

Abstract: Myocyte apoptosis is considered a major mechanism in the pathogenesis of heart failure. Accordingly, manipulations that inhibit apoptosis are assumed to preserve cardiac function by maintaining myocyte numbers. We tested this assumption by examining the effects of caspase inhibition (CI) on cardiac structure and function in C57BL/6 mouse with pressure overload model induced by transverse aortic constriction (TAC). CI preserved left ventricular (LV) function following TAC compared with the vehicle. TAC increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
1
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 32 publications
3
12
1
1
Order By: Relevance
“…Given that 75 % of the cells in the heart are non-myocytes [17], we discriminated the effects of the cardiomyopathy and its rescue with DN-Mst1 on myocyte vs. non-myocyte apoptosis. The finding that apoptosis predominantly occurred in non-myocytes and DN-Mst1 predominantly rescued non-myocyte apoptosis, supports the hypothesis that DN-Mst1 protects against necrosis, since non-myocytes, e.g., fibroblasts, macrophages, neutrophils, endothelial cells [33, 34, 36, 40], are all known to be involved in inflammation [9, 18, 39], which is more closely coupled to necrosis, rather than apoptosis [7, 10, 20, 22, 29, 38]. In further support of the role of necrosis, we also found that myocardial fibrosis, which is generally thought to be an outcome of necrosis rather than apoptosis [3, 10], was also rescued in the bigenic mice.…”
Section: Introductionsupporting
confidence: 54%
“…Given that 75 % of the cells in the heart are non-myocytes [17], we discriminated the effects of the cardiomyopathy and its rescue with DN-Mst1 on myocyte vs. non-myocyte apoptosis. The finding that apoptosis predominantly occurred in non-myocytes and DN-Mst1 predominantly rescued non-myocyte apoptosis, supports the hypothesis that DN-Mst1 protects against necrosis, since non-myocytes, e.g., fibroblasts, macrophages, neutrophils, endothelial cells [33, 34, 36, 40], are all known to be involved in inflammation [9, 18, 39], which is more closely coupled to necrosis, rather than apoptosis [7, 10, 20, 22, 29, 38]. In further support of the role of necrosis, we also found that myocardial fibrosis, which is generally thought to be an outcome of necrosis rather than apoptosis [3, 10], was also rescued in the bigenic mice.…”
Section: Introductionsupporting
confidence: 54%
“…However, the current results are consistent with our previous findings that the apoptosis occurs predominantly in nonmyocytes in several models of cardiomyopathy, including ischemic cardiomyopathy (50) and hypertrophic cardiomyopathy (18,51). Based on our previous studies, the cell types of apoptotic nonmyocytes mainly include macrophages, neutrophils, fibroblasts, and endothelial cells (50,51). The role of nonmyocyte apoptosis in the heart in mediating or preventing the cardiomyopathy is not clear, since the nonmyocytes are a double-edged sword.…”
Section: Discussionsupporting
confidence: 90%
“…Whereas this might be understood, recognizing that over 70% of cells in the heart are nonmyocytes, it seems inconsistent with the currently held concept that apoptosis leads to cardiac dysfunction through reducing myocyte numbers (4,19). However, the current results are consistent with our previous findings that the apoptosis occurs predominantly in nonmyocytes in several models of cardiomyopathy, including ischemic cardiomyopathy (50) and hypertrophic cardiomyopathy (18,51). Based on our previous studies, the cell types of apoptotic nonmyocytes mainly include macrophages, neutrophils, fibroblasts, and endothelial cells (50,51).…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…5μm thickness of serial heart tissue sections were used for histological assessment and immunohistochemical staining. In order to discriminate proliferation in non-myocytes and myocytes, tissue sections were counterstained with wheat germ agglutinin (WGA) Alexa Fluor-488 conjugate (Invitrogen) or troponin I, a myocyte marker, as described in our previous study [22]. …”
Section: Methodsmentioning
confidence: 99%